Método montessori y su aporte en el aprendizaje lúdico de los estudiantes de 3ro EGB de la Unidad Educativa Adolfo Páez del Cantón Echeandía - Ramos Montes, Cinthya Ninibeth (2023)
Nowadays, teaching methods and mechanisms have changed and students need new ways to learn in a more meaningful way and this leads us to analyze the methods used by the teacher. The objective of this research is to theoretically analyze the Montessori method and its contribution to the playful learning of 3rd EGB students of the Adolfo Páez Educational Unit of the Echeandía Canton. Throughout this research, the methods applied were the qualitative-quantitative approach, with the exploratory and descriptive level, the modality was documentary bibliographic research and field research. The techniques were the interview whose instruments were the questionnaire applied to the teachers of the Educational Unit. The results obtained show that the majority of teachers are interested in the application of more teaching methods that generate independence in students through play. Others are aware of the value and importance of the Montessori method and playful learning, and they also showed interest. By working with these didactic strategies within playful learning, participation is direct and encourages autonomy. The conclusions refer to having a specific theoretical foundation of the variables in order to effectively develop the Montessori teaching method that contributes to the application of playful learning for students and that in this way significant and quality learning occurs.